Special papersHerpes progenitalis – prevention of herpes simplex virus infections - Biało-Wójcicka, Ewelina; Majewski, Sławomir; Łoza, Katarzyna (Dermatology Review/Przegląd Dermatologiczny, 2015)
Genital herpes is one of the most common sexually transmitted viral diseases and the most common cause of mucosal erosions and ulcerations in the genital area. According to epidemiological data, the infection caused by genital herpes virus is common in developing countries. The number of sexually transmitted infections is increasing, and infections caused by herpes simplex virus 1 (HSV-1) in the genital area are becoming more common. In Poland there are no current epidemiological data on these infections. Genital herpes infection is dangerous for pregnant women, who can transmit it to infants. There is a significant risk of primary infection in pregnant women, transmitted by their seropositive partners. The early diagnosis and treatment are of utmost importance. The effective method of prevention and treatment is aciclovir, which in numerous studies was proven to be safe in pregnancy. In the article, the course of infection, treatment and prevention, especially in pregnant women and newborns, are discussed.